2015
DOI: 10.1111/crj.12359
|View full text |Cite
|
Sign up to set email alerts
|

A RCT of telehealth for COPD patient's quality of life: the whole system demonstrator evaluation

Abstract: Declaration of InterestAll authors have completed the Unified Competing Interest form at http://www.icmje.org/coi_disclosure.pdf (available on request from the corresponding author) and declare: no support from any organisation for the submitted work; no financial relationships with any organisations that might have an interest in the submitted work in the previous three years, no other relationships or activities that could appear to have influenced the submitted work." 2 AbstractIntroduction/Objectives:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 25 publications
3
25
0
Order By: Relevance
“… 24 In a recent randomised controlled trial (RCT), a more extensive assessment of QoL and psychological outcomes was performed on the COPD cohort of the WSD. 25 The findings from the RCT 25 are consistent with the above conclusion made by Cartwright and colleagues. 24 However, the RCT found no reductions in patients’ QoL in the longer term.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“… 24 In a recent randomised controlled trial (RCT), a more extensive assessment of QoL and psychological outcomes was performed on the COPD cohort of the WSD. 25 The findings from the RCT 25 are consistent with the above conclusion made by Cartwright and colleagues. 24 However, the RCT found no reductions in patients’ QoL in the longer term.…”
Section: Introductionsupporting
confidence: 88%
“…In contrast, there was a trend towards improved QoL and mood in the telehealth group at longer-term follow-up, but not at the short-term follow-up, as observed through disease-specific measures. 25 …”
Section: Introductionmentioning
confidence: 99%
“…15 Moreover, an RCT by Rixon et al found no reductions in COPD patients' HRQoL in the longer term by a telehealth intervention, observed through diseasespecific measures. 36 In a recent paper by Tupper et al, a 6-month telehealth intervention significantly improved HRQoL, assessed by a health-related QoL questionnaire (15D©) and the COPD Assessment Test (CAT), compared to the control group. 37 Notably, subjects included presented with advanced COPD; indeed, 86% of the subjects were stage 3 or 4 and the subjects were considered at high risk of exacerbations.…”
Section: Discussionmentioning
confidence: 98%
“…A common feature of these studies is that as patients spend more time using telemedicine devices, their disease management ability, quality of life and emotional improvement also increase. Rixon et al [45] also demonstrated the viewpoint.…”
Section: The Application Of Telemedicinementioning
confidence: 92%